Ultrasonographic scores for ileal Crohn’s disease assessment: Better, worse or the same as contrast-enhanced ultrasound? - M. Freitas (BMC Gastroenterology, 2022)
Abstract Background Intestinal ultrasound (IUS) is an increasingly used non-invasive tool to evaluate Crohn’s disease (CD) activity. Recently, two IUS scores that evaluate inflammatory activity have emerged: the Simple Ultrasound Activity Score for CD (SUS-CD) and the International Bowel Ultrasound Segmental Activity Score (IBUS-SAS). We aimed to compare the accuracy of SUS-CD, IBUS-SAS and contrast-enhanced ultrasound (CEUS) in predicting inflammatory activity in the terminal ileum in ileocolonoscopy in CD patients. Methods Retrospective study including all consecutive CD patients submitted to IUS with CEUS directed to the terminal ileum performed by a single operator between April 2016 and March 2020. Segmental SUS-CD and IBUS-SAS were calculated. A time-intensity curve of the contrast bowel wall enhancement was created with measurement of peak intensity using CEUS. The CD endoscopic activity in ileocolonoscopy was graded by Simple Endoscopic Score for CD (SES-CD) as inactive (SES-CD < 7) or active (SES-CD ≥ 7). Results Fifty patients were included, 54.0% were female, with mean age of 34 ± 12 years, and most had isolated ileal disease (60.0%), and a nonstricturing, nonpenetrating behaviour (44.0%). Most of the patients (60.0%) had active endoscopic disease (SES-CD ≥ 7). SUS-CD and IBUS-SAS were not different between patients with active or inactive endoscopic disease (p = 0.15; 0.57, respectively), having a poor accuracy to correlate endoscopic activity (area under de curve (AUC) 0.62; 0.55, respectively). Peak intensity in CEUS was significantly different in patients with active or inactive endoscopic disease (p = 0.004), having a good accuracy to correlate endoscopic activity (AUC 0.80). Conclusion Unlike CEUS, SUS-CD and IBUS-SAS were not able to accurately correlate endoscopic activity in terminal ileum in CD. Therefore, CEUS is a non-invasive emerging method that should be increasingly integrated in the ultrasonographic evaluation of CD patients.